Income fluctuations and subjective well-being: Partially mediating effects of remittances - Azizbek Tokhirov (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2023)
I investigate the consequences of income fluctuations caused by commodity price changes on happiness levels in regions specialising in export agriculture. Using a difference-in-differences framework, I compare subjective well-being patterns of households living in cotton and non-cotton geographical areas of Tajikistan before and after the 2010/11 cotton price increase. The results indicate that exposure to income fluctuations, even to a positive one, is associated with a notable decrease in the reported levels of financial and overall life satisfaction. The well-being changes are mainly observed between households engaged in agricultural employment, the number of which became larger only in cotton regions in response to the shock. The results of triple difference-in-differences estimations reveal that remittances mediate the negative effects of export price fluctuations but only on financial satisfaction, suggesting that a mere compensation of income losses does not fully restore subjective well-being.
Keywords: I31; Q02; 330; subjective well-being; export prices; household income; remittances